Product market regulation, firm selection and unemployment - Gabriel Felbermayr; Julien Prat (Institute for the Study of Labor (IZA), 2007)
This paper analyzes the effect of Product Market Regulation (PMR) on unemployment in a search model with heterogeneous multiple-worker firms. In our setup, PMR modifies the distribution of firm productivities, thereby affecting the equilibrium rate of unemployment. We distinguish between PMR related to entry costs and PMR that generates recurrent fixed costs. We find that: (i) higher entry costs raise the rate of unemployment mainly through our novel selection effect, (ii) higher fixed costs lower unemployment through the selection effect and increase it through the competition effect analyzed in Blanchard and Giavazzi (2003). We propose econometric evidence consistent with the unemployment effects of sunk versus recurring costs.
urn:nbn:de:101:1-20080402206
Keywords: 330; Regulierung; Markteintritt; Theorie der Arbeitslosigkeit; Arbeitsuche; Beschäftigungseffekt; Theorie